CCT020312 Inhibits Triple-Negative Breast Cancer Through PERK Pathway-Mediated G1 Phase Cell Cycle Arrest and Apoptosis - Li, Xiaoli; Yu, Xiaoping; Zhou, Duanfang; Chen, Bo; Li, Wenjun; Zheng, Xiangru; Zeng, Hongfang; Long, Liangyuan; Zhou, Weiying (Frontiers in Pharmacology, 2020)
Triple-negative breast cancer (TNBC) has a poor prognosis due to the lack of specific therapeutic targets. CCT020312, a selective eukaryotic translation initiation factor 2 alpha (eIF2α)/protein kinase RNA-like endoplasmic reticulum kinase (PERK) activator, may have a potent anti-tumor effect. In the present study, we examined the effects of CCT020312 on TNBC and explored the underlying mechanism. We found that CCT020312 inhibited the viability of TNBC cell lines, MDA-MB-453 and CAL-148, by inducing apoptosis and G1 phase cell cycle arrest. CCT020312 decreased the protein levels of cyclin-dependent kinase 4 (CDK4), CDK6, cyclin D1, and B-cell lymphoma 2 (Bcl-2) and increased the levels of Bcl-2-associated X protein (Bax) and cleaved poly (ADP-ribose) polymerase (PARP) compared with those in the control. CCT020312 activated PERK/eIF2α/activating transcription factor 4 (ATF4)/CCAAT-enhancer binding protein (C/EBP) homologous protein transcription factor (CHOP) signaling and inhibited protein kinase B (AKT)/mammalian target of rapamycin (mTOR) signaling. Furthermore, CCT020312 inhibited tumor growth in an MDA-MB-453 orthotopic xenograft mouse model by activating the PERK/eIF2α/ATF4/CHOP pathway and inhibiting the AKT/mTOR pathway. Thus, our study shows that CCT020312 may be a potential drug candidate for TNBC treatment.